From Transitional to Transformative Justice: A New Agenda for Practice. (14th August 2014) - Gready, Paul; Robins, Simon
Abstract 1 : Transitional justice has become a globally dominant lens through which to approach states addressing legacies of a violent past. An industry of praxis has emerged, supported by dedicated nongovernmental organizations and large-scale funding from western donors. Yet, the performance and impact of transitional justice mechanisms have been at best ambiguous and at times disappointing. This article proposes a new agenda for practice, one that offers a concept of justice that is more 'transformative' than 'transitional.' The article starts by setting out the limitations of transitional justice, and recent responses to these limitations in transitional justice practice. A definition of transformative justice draws on this discussion as well as insights from related fields such as peace building and conflict transformation . A final section of the article, on tools for transformative justice, provides practical guidance on how to implement a more transformative transitional justice.